(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
Classrooms across the world are filled with students who are consistently told to listen, asked to listen, and forced to listen without any preparation for knowing how to listen. Teaching students how to become mindful listeners can enhance their ability to learn to listen. Mindful listening is a form of active listening that goes beyond merely hearing words or sounds; it involves being fully present and engaged. The chapter also contains an overview of the types of listening and stages of listening for beginning listening instruction practices in the elementary classroom and concludes with giving teachers strategies for creating their own listening journey to understand how and why there is a need to transition from telling students to listen to teaching them how to listen in elementary classrooms. Mindful listening can enhance students’ communication skills, help them build healthy relationships, and improve their achievement not only in school but also in life. Overall, helping students to practice mindful listening can enhance both the teacher and the learners to become more productive and heard. By engaging in mindful listening, teachers can foster better connections, improve communication, and develop deeper understanding and empathy not only for their students, but also for themselves. In this article, you can also learn how to improve students’ listening skills from elementary school and about its effective methods. Listening can enhance students’ communication skills, help them build healthy relationships, and improve their achievement not only in school but also in life. Overall, helping students to practice mindful listening can enhance both the teacher and the learners to become more productive and heard. In this article, you can also learn how to improve students’ listening skills from elementary school and about its effective methods.